Phleomycin-Induced Solubilization of Deoxyribonucleic Acid in Uninfected and T Bacteriophage-Infected Escherichia coli B - Shive, Karen (1976)
Phleomycin (PM) induces rapid solubilization of deoxyribonucleic acid (DNA), inhibition of cellular mass increase, and loss of viability when added either to growing cultures of Escherichia coli B or an endonuclease I-defective derivative of B. Nonetheless, bacteriophage of the T-even series are produced, albeit to a reduced extent, when PM is added with phage or after infection to E. coli cells. Bacteriophage T4 infection inhibits the ability of PM to bring about the solubilization of DNA; this effect appears to account for most of the resistance of T-even phage replication to PM. The patterns of inhibition of phage yields obtained when PM is added at infection suggest that glucosylation of T-even phage DNA may also have a protective effect. However, PM induces the solubilization of glucosylated and nonglucosylated DNA at approximately the same rate and thermal denaturation studies indicate that the antibiotic binds both types of DNA equally well. The latter experiments also provided evidence that PM dissociates from DNA at temperatures greater than 80 C.